Reverse Mentoring: Transforming Learning at Individual, Team, and Organizational Levels to Build Belonging in the Workplace - Gordon, Patrice (International Journal of Human Resource Development Practice Policy & Research, 2025)
As the modern workplace undergoes rapid transformation, traditional learning approaches are increasingly insufficient in addressing the complexities of a multigenerational workforce. With as many as six generations now coexisting within organisations — from the Silent Generation (1928–1945), Baby Boomers (1946–1964), Gen X (1965–1980), Millennials (1981–1996), and Gen Z (1997–2012), to the emerging influence of Gen-AI, there is a critical need for innovative learning strategies. Reverse mentoring has emerged as a structured approach to fostering cross-generational and experiential learning, promoting inclusivity, innovation, and adaptability. This paper provides a historical overview of reverse mentoring, examines the predominantly qualitative research conducted in this domain, and presents a comprehensive framework for the effective design and implementation of reverse mentoring programmes within organizational contexts.